ESTABLISHMENT OF THE STATE OF SPINE DEFORMITY IN STUDENTS OF THE SECONDARY SCHOOL "IVAN-GORAN KOVAČIĆ", HERCEG NOVI - Grujo Bjeković; Arnaut Đorđe (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Subject of this research is establishment of a spine deformity existence in students of the secondary school "Ivan-Goran Kovačić" based in Herceg Novi, and the school role in their removal. The aim of the research is to provide actual knowledge and results about grow, growth and body posture conditions of students at the secondary school "Ivan-Goran Kovačić"in Herceg Novi. The sample is represented by 115 students, assigned in four classes. The selected sample is made of four classes, out of which is one from each grade, i.e. first, second, third and fourth grade. Those classes represent the student population in the whole school. Variables in this research, at the selected sample of students, are follows: spine deformities, lordosis, kyphosis and scoliosis. Analysis of the results obtained after the research has been completed shows that the functional stage of scoliotic deformity is presented at the majority students from the sample. The number of students with kyphosis and lordosis deformity of spine is considerably lower. Research results show that scoliotic, kyphotic and lordotic body postures are in the range of functional changes. Scoliosis deformities of spine were, as per the results, more presented in the female students than in the male students